UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN GAMIFIKASI BERBANTUAN KAHOOT SISWA KELAS II SEKOLAH DASAR - Rijal, Akmal; Maharani, Tidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the low mathematics learning outcomes of grade II students in mathematics learning at SD Negeri II Wonosari. This research aims to improve the learning outcomes of mathematics students in grade II by using the kahoot-assisted gamification model. This type of research is classroom action research (PTK). Data collection techniques are carried out by observation, interviews, tests and documentation. The data analysis techniques used are quantitative descriptive. This research consists of 2 cycles using the Kemmis & McTaggart model which includes planning, implementation of actions, observation, and reflection. The results of the study showed an increase in student learning outcomes after the implementation of the Kahoot-assisted gamification model. In the first cycle, the percentage of students who completed was only 16.67%, in the second cycle it rose to 62.50%, and the percentage of classical completeness had been achieved. This shows that there is an improvement in mathematics learning outcomes through the implementation of the Kahoot-assisted gamification model in Year II students of SD Negeri 3 Wonosari.